Phagocytosis Main Key of Immune System - Shamsadin Athari, Seyyed; Mehrabi Nasab, Entezar (Physiology, 2023)
Phagocytosis, as an innate immune defense mechanism, is the first process to respond to pathogens. It is also one of the initiating branches of an adaptive immune response. This book provides a comprehensive overview of phagocytosis and related cells in the immune response. It presents the basics of phagocytosis as well as discusses management and therapeutic strategies for infections.